Deformation and stability analysis of a cut slope / Masyitah Md Nujid - Md Nujid, Masyitah (Universiti Teknologi MARA, Perlis, 2012)
A cut slope is subjected to deform and fail during or after construction activities despite the limit equilibrium analysis done during the design process indicate that the designed slope would have a factor safety greater than one. Deformation occurred during and after the excavation yields an additional stress or reduction in the strength of the soil. The objectives of this research are to assess the deformation pattern of soil or slope face induced by cutting, to evaluate the stability of a slope based on shear strength reduction technique and to compare factor of safety results obtained by shear strength reduction technique (SRT) in Plaxis 7.2 and limit equilibrium method (LEM) in SLOPE/ W. The deformation pattern of the natural slope and the cut slopes were analyzed using finite element program in Plaxis 7.2 which soil behavior was modeled as a simple Mohr-Coulomb. Furthermore the stability of these slopes were evaluated based on shear strength reduction technique. Stability analysis was also done on the final cut slope where failure has occurred at this stage using limit equilibrium method (LEM) in SLOPE/W. It was observed that the deformation pattern was significantly affected by slope angle and soil strength. The factor of safety calculated using different computer program gave some differences due to the assumptions and limitations used in the analysis.